Retention in Care among Patients with Early HIV Disease in Haiti. (November 2017) - Hennessey, Kelly A.; Leger, Taina Dadaille; Rivera, Vanessa R.; Marcelin, Adias; McNairy, Margaret L.; Guiteau, Colette; Devieux, Jessy G.; Marcelin, Yvel; Charles, Benedict; Cremieux, Pierre-Yves; Koenig, Serena P.; Pape, Jean W.
In September 2015, the World Health Organization updated their guidelines to recommend antiretroviral therapy (ART) for all people living with HIV. Countries are now in the process of implementing strategies to provide universal HIV treatment. We analyzed the rate of retention and time to ART eligibility (according to 2013 WHO guidelines) among 3, 345 adult patients receiving positive HIV test results between February 1, 2003 and March 31, 2013 at the GHESKIO Clinic in Haiti, with WHO stage 1 or 2 disease and initial CD4 cell count >500 cells/mm3. Among the 3, 345 patients, 2, 423 (72%) were female, the median age was 33 years, 3, 089 (92%) lived in Port-au-Prince, and 1, 944 (58%) had attended no school or primary school only. The median initial CD4 cell count was 668 cells/mm3 (IQR: 572-834); over the subsequent 2 years, 1, 485 patients (44%) were lost to follow-up and 7 (<1%) died pre-ART, 1, 041 (31%) were retained in pre-ART care, and 819 (24%) initiated ART. In multivariate analysis, secondary education (aOR 1.27; 95% CI: 1.10-1.47), female gender (aOR: 1.28; 95% CI: 1.09-1.50), co-habitation (aOR: 1.31; 95% CI: 1.09-1.57), and residence in Port-au-Prince (aOR: 1.43; 95% CI: 1.09-1.88) were associated with retention in care. The median time from baseline CD4 count to ART eligibility was 1.7 years. Prior to the implementation of universal treatment, pre-ART attrition was high among patients who did not qualify for ART at presentation. Though implementing WHO recommendations for universal ART will require service expansion, it will likely result in improved retention for those at risk of being lost to follow-up.